Dynamics of bacterial communities and substrate conversion during olive-mill waste dark fermentation: Prediction of the metabolic routes for hydrogen production. (January 2021) - Mugnai, Gianmarco; Borruso, Luigimaria; Mimmo, Tanja; Cesco, Stefano; Luongo, Vincenzo; Frunzo, Luigi; Fabbricino, Massimiliano; Pirozzi, Francesco; Cappitelli, Francesca; Villa, Federica
Graphical abstract: Highlights: Substrate conversion routes during OMW dark fermentation are unknown. Bacillus and Clostridium were the most abundant phylotypes during the H2 production. Lactate fermentation was the main H2 -producing route. H2 was produced through the recycling of electron carriers via the PFOR pathway. The synergy among lactate-, acetate, and H2 -producing bacteria was reported. Abstract: The aim of this work was to study the biological catalysts and possible substrate conversion routes in mesophilic dark fermentation reactors aimed at producing H2 from olive mill wastewater. Bacillus and Clostridium were the most abundant phylotypes during the rapid stage of H2 production. Chemical analyses combined with predictive functional profiling of the bacterial communities indicated that the lactate fermentation was the main H2 -producing route. In fact, during the fermentation process, lactate and acetate were consumed, while H2 and butyrate were being produced. The fermentation process was rich in genes that encode enzymes for lactate generation from pyruvate. Lactate conversion to butyrate through the generation of pyruvate produced H2 through the recycling of electron carriers via the pyruvate ferredoxin oxydoreductase pathway. Overall, these findings showed the synergy among lactate-, acetate- and H2 -producing bacteria, which complex interactions determine the H2 production routes in the bioreactors.